CROPPING SYSTEM AND FERTILIZER TYPE ON GROWTH AND YIELD OF CABBAGE - Mohammed, Serrl Abdul Kareem; Manea, Ali Ibadi (International Journal of Psychosocial Rehabilitation, 2020)
Less synthetic fertilizer is being used to grow cabbage (Brassica oleracea var. capitata L.) in a more sustainable manner. Increasing food production can no longer depend only on increased yield. Monocropping may not be the most efficient way to produce cabbage; intercropping may be a better way of managing available land. The study was carried out Babylon, Iraq, to evaluate performance of cropping systems, and fertilizer type, on growth of monocropped cabbage compared to intercropping cabbage with broad bean (Vicia faba L.). Fertilizer treatments were organic palm or rice residuals (each 20 Mt∙ha-1) or synthetic fertilizer (300 kg∙ha-1 18N:18P:18K) control. Monocropped cabbage with the control fertilizer treatment produced the longest leaves, and the heaviest heads. Intercropping cabbage with palm residual produced the most wrapper leaves, greatest leaf area and the highest Vitamin C content. Intercropping cabbage and the control fertilizer produced the highest percent of chlorophyll and carotenoids. Intercropping cabbage with rice residual produced the heaviest heads, most marketable yield and highest percent of nitrogen and protein. Depending on production goals intercropping cabbage with beans and synthetic or organic fertilizer can be used to improve cabbage yield.